Penerapan Manajemen Produksi Dalam Meningkatkan Produktifitas Komoditi Lokal: Desa Wirotaman, Kecamatan Ampelgading, Kabupaten Malang - Budi Iriani Yudaningrum; Indah Datin Nadliroh; Anudiyan Amir Mas'ud; Astuti; Putri Dia Ayu; Alma Nur Andini (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2023)
In the supply market, a product is a crucial component. Then, one of the crucial elements in a manufacturing process for goods that the firm will sell is product quality. Problems with product quality have a significant impact on market share value. The goal of this essay is to determine how crucial product quality is to gaining market share and, ultimately, profitability for the business. This work uses descriptive-qualitative data analysis, reading and processing sources from journals, books, and articles that are earlier studies before using them as research material.The discussion of this article has revealed that product quality, particularly coffee production management, has a significant impact on customer happiness, which increases customer loyalty and helps the business. In this instance, it may be claimed that coffee's product quality affects consumers' purchasing choices. Because of this, current coffee items must be of high quality in order to be considered effective tools for competing with other goods.